Efficient approaches to the treatment of acute gastroenteritis in children - M. K. Bekhtereva; V. V. Ivanova; A. M. Komarova; S. G. Semenova (Медицинский совет, 2015)
Acute intestinal infection (AII) is the 2nd most widespread infectious disease in children after acute respiratory infection, and a relevant healthcare problem. The incidence of infectious diarrhea in Russia varies greatly: for example, in St. Petersburg, the incidence of rotavirus gastroenteritis in children under the age of 14 is more than 700 per 100 thousand of the same age, and the incidence of norovirus gastroenteritis in 2014 reached 110 per 100 thousand children younger than 14 years (Rospotrebnadzor St. Petersburg). In Europe, from 0.5 to 1.9 episodes of infectious diarrhea in children under the age of 3 are registered annually [1, 2].